Characterization, subsite mapping and N-terminal sequence of miliin, a serine-protease isolated from the latex of Euphorbia milii - Moro, L. P. [UNESP]; Cabral, H.; Okamoto, D. N.; Hirata, I.; Juliano, M. A.; Juliano, L.; Bonilla-Rodriguez, G. O. [UNESP] (Elsevier B.V., 2013)
Miliin is a serine protease purified from the latex of Euphorbia milii. This work reports the effect of pH and temperature on the catalytic activity of miliin, using fluorescence resonance energy transfer (FRET) substrates. Miliin displayed the highest activity at pH 9 and 35 degrees C. Subsite mapping shows that subsites S-2 to S-2' prefer uncharged residues. The S-2 subsite prefers hydrophobic aliphatic amino acids (Val, Pro and Ile) and defines the cleavage site. This work is the first one that reports subsite mapping of Euphorbiacea proteases. The N-terminal sequence showed higher similarity (40%) with the serine protease LIM9 isolated from Lilium. The presence of Tyr, Pro and Lys at positions 2, 5 and 10 respectively, were observed for most of the serine proteases used for comparison. The N-terminal sequence has striking differences with those reported previously for milin and eumiliin, other serine proteases isolated from the latex of E. milii. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Euphorbia milii; Miliin; Subsite mapping; Serine protease; Plant protease; FRET substrates